Land use changes in the area of Movraški Kras and adjacent flysch areas between 1830 and 2008 - Ivajnšič, Danijel; Škornik, Sonja; Kaligarič, Mitja (Journal for Geography, 2013)
Agricultural landscape, as a result of human interference and management, has drastically changed in the last 180 years within the area. The process of land abandonment is the most evident, along with overgrowing of grasslands, field fragmentation and spreading of urban surfaces. The changes are explained with drastically changed socio-economic drivers in the area. Here we compare changes in land-use categories between the years 1830 and 2008 on the flysch and limestone substrate. Historical data from the “Carta Corografica del Litorale” were obtained and compared with the habitat mapping based on the PHYSIS typology in the year 2007/08. Surprisingly, the overgrowing process was more pronounced within the limestone part of the area.